2017
DOI: 10.1504/ijlsm.2017.080628
|View full text |Cite
|
Sign up to set email alerts
|

How do different supply chain configuration settings impact on performance trade-offs?

Abstract: Abstract:The notion of 'fit' in the supply chain management (SCM) literature has evolved following the adoption of the contingency approach in an endeavour to achieve greater organisational effectiveness. In this paper, we investigate the possible approaches to achieving a state of fit between supply chain configuration settings and performance indicators, while taking into account the contextual factors related to different industry sectors and geographical dispersion levels. This study addresses the pressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Contingency theory (Lawrence and Lorsch, 1967) argues that no theory or method can be applied in all instances, and companies have to adapt their structures to maintain fit with changing contextual factors (Ellram and Cooper, 2014;Sabri et al, 2017). First, market-related factors (i.e.…”
Section: The Influence Of Contextual Factors On Tc and Lcmentioning
confidence: 99%
See 1 more Smart Citation
“…Contingency theory (Lawrence and Lorsch, 1967) argues that no theory or method can be applied in all instances, and companies have to adapt their structures to maintain fit with changing contextual factors (Ellram and Cooper, 2014;Sabri et al, 2017). First, market-related factors (i.e.…”
Section: The Influence Of Contextual Factors On Tc and Lcmentioning
confidence: 99%
“…Zeng and Rossetti, 2003;Lorentz et al, 2013). In today's context characterised by growing demand in speed and flexibility, aligning LC with TC is paramount when shaping companies' global strategy (Sabri et al, 2017;Harris et al, 2018). On the one hand, logistics is a key enabler for company internationalisation (Marchet et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since the seminal work of Fisher (1997), there has been a growing interest in customising the configuration so that it suits the supply chain's contextual environment. Hence, it is important to take into account key factors such as level of localisation and globalisation (Ebben and Johnson, 2005;Bhatnagar and Sohal, 2005;Kirca et al, 2012), which was found to have a major influence on supply chain performance (Sabri et al, 2017). Supply chain configuration is usually conceptualised in terms of several structural elements, such as the number of actors within the chain, geographical dispersion level, collaboration and inter-organisational relationships, and supply and distribution network design (Chandra and Grabis, 2007;Sezen, 2008;Chopra and Miendle, 2012;Corominas et al, 2015).…”
Section: Supply Chain Configurationmentioning
confidence: 99%
“…As such, the configuration deals with the coordination of products, processes, and logistics decisions (Zheng et al, 2010). Supply chain configuration can be developed based on one of three approaches; product characteristics, process, or systems thinking (Sabri et al, 2017).…”
Section: Supply Chain Configurationmentioning
confidence: 99%
See 1 more Smart Citation